Discurso político de Lula: o papel do marcador não na construção da persona textual - Correa, Erick Kader Callegaro (2015)
When we produce meaning within the various contexts in which we found ourselves, we are assessing the world around us, either positively or negatively. However, we do not just evaluate through typical elements such as attributes and adverbial structures. We also evaluate though the engagement we built upon the texts of others. Linguistic resources as the negative marker "no", an indicator of negative polarity (HALLIDAY; MATTHIESSEN, 2004 2014) also constitutes itself an element with highly evaluative potential. From the modality system the negative item no provokes dialogic contraction, whose rhetoric effect is the closing of the dialogic space in relation to the proposition that it accompanies: the speaker uses the negation to devalue, take in as untrue or invalidate propositions produced previously to his/her text. In this study, we aim to locate, analyze and categorize the frequency of usage of the lexicogrammar item "no" in 107 speeches from Brazil‟s the ex-president Lula Inácio Lula da Silva, made in the first semester of his first mandate (2003-2006) and through criteria established, we selected one speech, called Speech of the President of the Republic, Luiz Inácio Lula da Silva, when visiting Itaici s Retirement House CNBB, delivered on May 1st 2003. Processed by WordSmith Tools 6.0 (SCOTT, 2006), it was found 175 occurrences of the word "no" and it was classified the most used word in the text. From these data and through the studies of the negation phenomenon in Halliday and Matthiessen (2014) Martin and White (2005), Pagano (1994), Tottie (1987), we proposed five types of negation through the functional usage of the negative marker "no": when the locus of negation is upon a projecting clause, Lula chose between direct/propositional negative or transferred/modal negation; when the locus of negation is upon a projected clause, Lula chose amongst direct/propositional negation, transferred/modal negation or gradual negation. Then, we provided hypotheses about the textual persona that Lula created through such speeches with the meaningful usage of negation and identify the political strategies, regarding to his ethos that helped him achieve 87% of popularity and satisfaction amongst the Brazilian population. Our first hypothesis is that the meaningful usage of negation is the invalidation that the new former president does on the acts of previous government. When denying, Lula reinforces the thesis that his government, once affiliated to the Workers‟ Party, is different from others. Such idea feeds the public the hope that under his management, Brazil can become a more democratic nation, in which the errors of the past will not be repeated and that lower classes will be remembered by the Public Power. Textual persona and ethos are also presented as aware of problems and conditions of social and economical areas of society: the constant usage of negation reveals that Lula urges to correct his public in terms of knowledge about Brasil, bringing awareness of issues that were never mentiored or discussed before by politicians.